HOUSING TENURE SECURITY IN RTLH PROGRAM OF SURAKARTA INDONESIA- HOW CAN IT CONTRIBUTE TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS OF POST-2015 AGENDA? - Winny Astuti (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2019)
This paper evaluated the Program of Substandard Housing (RTLH) Renovation proposed for the agenda of “Surakarta Informal Settlements Clearance 2015” for solving the problem of improving the quality of 6612 substandard houses. This research took case study in the small-scaled area of poor settlements in the prone area along riverbank of Bengawan Solo River namely Kelurahan Ketelan. How could this outcome contribute to achieve Sustainable Development Goals (SDGs) in terms of providing housing security to establish inclusive, safe, resilient and sustainable city and human settlement as stated by SDGs? The case study research was conducted by multiple methods of qualitative and quantitative analysis. The results showed that the program had the highest contribution on the improvement of sanitation, in terms of the use of septic tank (change value of 0.5750) and the use of toilet (0.203)as one of priorities of SDGs. However,there was only little contribution in increasing access to land tenure security ( 0.002); It was surprising that the improvement of housing construction itself was not high. This program involved the collaboration among state-civil-society-community and other development parties and increased channeling assistance for settlements sustainability and poverty reduction